The Harmony of Carbon Emission, Environmental Performance, Social Performance, and Leverage - Khairunnisa; Firdaus Abdul Rahman (Universitas Pamulang, 2026)
This study explores the relationship between gas emissions, environmental performance, social performance, and the moderating role of leverage in the relationship. This study was conducted in one of the developing countries, namely Indonesia. This study uses a sample of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The sample used in this study was 165 samples. This study uses Stata software to process data, with random effect models. The study results indicate that the relationship between gas emissions and the environment has a positive and significant effect. The moderation variable in this study cannot have an impact on environmental performance and social performance. This study contributes to the literature on how companies can invest in gas emissions and influence environmental performance.